Обґрунтування вибору стратегії фінансового оздоровлення промислового підприємства - Федоренко, Ірина Анатоліївна; Сисоєв, Володимир Вікторович; Самохіна, Світлана Сергіївна (Причорноморський науково-дослідний інститут економіки та інновацій, 2021)
У статті проаналізовано критерії вибору стратегії фінансового оздоровлення на окремих етапах антикризового управління промисловим підприємством. Визначено, що під час використання санаційних заходів фінансового оздоровлення може відбуватися перепрофілювання виробництва, реорганізація промислового підприємства, продаж неефективного пакету акцій і частин у статутному капіталі інших підприємств, оптимізація роботи штату співробітників, його чисельності, збільшення власного статутного капіталу. Розглянуто етапи фінансового оздоровлення промислового підприємства, що мають прямий вплив на досягнення стратегічних цілей та фінансову стійкість підприємства; запропоновано впровадити бізнес-план та форму плану санації за розділами в процесі вирішення оставлених функціональних завдань моделювання оцінки, прогнозування, сценарного планування і контролю інноваційних процесів.

The article analyzes the criteria for choosing a strategy for financial recovery at certain stages of crisis management of an industrial enterprise. Theoretical issues of crisis management are considered and the main tool of its implementation is investigated – organizational and economic management mechanism (strategy), the development and implementation of which should positively affect the economic development of the enterprise through a quality approach to its production and financial potential. Drawing up and using the plan as an element of reorganization should ensure timely response to changes in the economy of the enterprise, analyze possible deviations from the plan and determine the target settings of the enterprise as a microeconomic system in the economy. It is determined that the use of rehabilitation measures of financial recovery may lead to re-profiling of production, reorganization of industrial enterprises, sale of inefficient shares and units in the authorized capital of other enterprises, optimization of staff, its number, increase of authorized capital. In the course of this study the stages of financial recovery of an industrial enterprise that have a direct impact on the achievement of strategic goals and f inancial stability of the enterprise are considered; it is proposed to introduce a business plan and the form of a reorganization plan by sections in the process of solving the set functional tasks of modeling assessment, forecasting, scenario planning and control of innovation processes. Based on the analysis of existing approaches to the financial recovery of industrial enterprises, it was found that there is a problem in the theory and practice of crisis management in the form of imperfect assessment of the feasibility of financial recovery. Thus, there is a need to improve the rehabilitation mechanism not only in terms of loss of solvency, but also to preserve and increase the potential of the enterprise. As good governance and strategic decisions can have a greater impact on the negative effects of crises, this determines the relevance and appropriateness of research
Justification of the choice of the strategy of financial recovery of the industrial enterprise
Keywords: стратегія; фінансове оздо ровлення; санація; антикризове управління; банкрутство; досудова санація; бізнес-план; strategy; financial recovery; reorganization; crisis management; bankruptcy; pre-trial reorganization; business plan